Analytical model and design formulae of circular CFSTs under axial tension. (June 2017) - Xu, Li-Yan; Tao, Mu-Xuan; Zhou, Meng
Abstract: A circular concrete-filled steel tube (CCFST) component is subjected to tension in certain practical engineering projects. Several past experimental programs have stressed that the apparent strength and stiffness enhancement phenomena observed in tensile circular steel tubes can be attributable to the filled concrete. In this study, an analytical model for describing the strength and stiffness enhancement of the circular steel tubes is developed. The interface performance between the steel tube and filled concrete is considered in the model. Based on the proposed analytical model, simplified design formulae for strength and stiffness enhancement coefficients are proposed. These design formulae indicate that the confining and fibre-reinforcing effects lead to the strength improvement, while the confining effect, fibre-reinforcing effect, and tension-stiffening effects all contribute to the stiffness enhancement. Then, a design procedure for determining the axial tensile strength and stiffness of CCFSTs is provided, and a design example is also demonstrated. The accuracy of both the proposed analytical model and design formulae are validated by the results of two groups of axial tension tests, which demonstrates that the full-process load-strain behaviour can be accurately captured by a bilinear model based on the proposed analytical formulae. Finally, analytical solutions for the longitudinal stress distributions of the steel tube and filled concrete are provided for a better understanding of the tension-stiffening effect. In addition, the contributions of different effects to strength and stiffness enhancements are quantitatively evaluated for all the test specimens. Highlights: An analytical model of CCFSTs under axial tension is proposed. The interface performance between the steel tube and filled concrete is theoretically modelled. The influences of the confining, fibre-reinforcing, and tension-stiffening effects are discussed. Design formulae for strength and stiffness enhancement coefficients are proposed. A design procedure for determining tensile strength and stiffness is provided and validated.